2007
DOI: 10.1093/ecam/nem056
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Anesthesia and Analgesia for Clinical Acute Pain in Japan

Abstract: Acupuncture anesthesia has been practiced in China since about 1960. In Japan, Hyodo reported 30 cases of acupuncture anesthesia in 1972. However, from around 1980, the direction of acupuncture investigations turned from anesthesia to analgesia. Acupuncture analgesia is presently considered a way to activate the body's endogenous analgesic system. Recently, with the rise of acupuncture as one of the most well known CAM therapies, acupuncture or moxibustion treatment has been reported for both acute and chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
1
22
0
Order By: Relevance
“…A major part of studies investigating the effect of AP have been related to pain assessment and the possible mechanisms behind the acupuncture analgesic effects have been reported elsewhere (CAO, 2002;HE, 1987;CHEN, 2008;MCLENNAN et al, 1977;KAVOUSSI;ROSS, 2007;MELZACK, 1976;MOON et al, 2007;OKADA;KAWAKITA, 2009;TAGUCHI, 2008;ZIJLSTRA et al, 2003). Acupuncture has been commonly used to treat acute and chronic pain (CAO, 2002;CASSU et al, 2008;FERRARI et al, 2006;HE, 1987;JOAQUIM et al, 2010;TAGUCHI, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major part of studies investigating the effect of AP have been related to pain assessment and the possible mechanisms behind the acupuncture analgesic effects have been reported elsewhere (CAO, 2002;HE, 1987;CHEN, 2008;MCLENNAN et al, 1977;KAVOUSSI;ROSS, 2007;MELZACK, 1976;MOON et al, 2007;OKADA;KAWAKITA, 2009;TAGUCHI, 2008;ZIJLSTRA et al, 2003). Acupuncture has been commonly used to treat acute and chronic pain (CAO, 2002;CASSU et al, 2008;FERRARI et al, 2006;HE, 1987;JOAQUIM et al, 2010;TAGUCHI, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been commonly used to treat acute and chronic pain (CAO, 2002;CASSU et al, 2008;FERRARI et al, 2006;HE, 1987;JOAQUIM et al, 2010;TAGUCHI, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has evolved from the belief that acupuncture effects are mediated via the production of central endorphins, through alteration to serotonin, norepinephrine and adenosine expression and by changes in muscle and skin blood flow. 7 Application in acute pain Acupuncture is used in Japan for postoperative pain, dental extraction pain and neuropathic pain, 8 but there are no qualitative studies done to make recommendations. A Cochrane review from 2006 reports good relief from nausea and vomiting but also concludes that there is no superiority of acupuncture over anti-emetics.…”
Section: Acupuncturementioning
confidence: 99%
“…Studies in Japan found an increase in the threshold of excitatory pain, but the plasma β-endorphins and ACTH levels in the cerebrospinal fluid did not increase after EA. The study concluded that other endogenous opioid peptides could be involved in acupuncture analgesia other than β-endorphins [6]. Harbach of acupuncture on patients with chronic low back pain, found that acupuncture had no effect on plasma β-endorphin levels [7].…”
Section: Introductionmentioning
confidence: 98%